Study on the stress and mechanism of self-separated GaN grown by Na-flux method. (4th February 2021) - Si, Zhiwei; Liu, Zongliang; Gu, Hong; Dong, Xiaoming; Gao, Xiaodong; Ren, Yujiao; Wang, Xiao; Wang, Jianfeng; Xu, Ke
Abstract: A 2 inch free-standing c -plane GaN wafer was fabricated through in situ self-separation using HVPE-seed crystal etching back (HCEB) by intentionally adjusting the nitrogen pressure in the Na-flux growth process of GaN. First, adjust the nitrogen pressure in the reactor to a lower level to facilitate HCEB to form a large number of voids at the interface between the c -plane HVPE seed and the c -plane Na-flux GaN. After regrowth of approximately 340  μ m thick Na-flux GaN, self-separation was achieved during the cooling process. The free-standing GaN wafer was almost stress-free as a result of strain relief by the in situ self-separation process, which was confirmed by room-temperature Raman and low-temperature photoluminescence measurements. It is supposed that the HCEB process can be applied to fabricate high-quality free-standing GaN wafers in the future.